BUILDING A STRATEGIC PARTNERSHIP WITH KAZAKHSTAN (A Blueprint for India’s Central Asia Policy) - STOBDAN, Phunchok (CENTRAL ASIA AND THE CAUCASUS, 2006)
India has not been able to make significant inroads into Central Asia, a region of vital strategic importance. Central Asia had a considerable impact on the polity and economy all through Indian history. Trade routes linking ancient Starpath to the Silk Road also carried Indian religion, philosophy and science beyond to Inner and Eastern Asia.1 The British India’s security and frontier trade policy with East Turkistan and Afghanistan is well known. People of Central Asian republics always looked toward India with fondness even while they were under Russian dominance or even when they became part of the Soviet system. The Soviet disintegration created fresh opportunities, with new states also looking toward India for political and economic sustenance. By opening missions in the five capitals, providing substantive development aid and technical support, several Prime Ministerial visits and cooperation agreements in diverse fields, India evolved its “extended neighborhood” policy but somehow it could not transcend its nostalgia for Soviet times. While Pakistani diplomacy in the region throughout the 1990s aimed at averting India’s reach to Central Asia, India was compelled to tread with caution lest the spread of Islamic fundamentalism and the Pakistani exploitation of the regional environment become detrimental to India’s interests. India supported a number of regional initiatives including India-Iran-Turkmenistan tripartite railway-line goodwill, India has not been able to make commercial progress in Central Asia or has achieved significant stakes in region’s strategic mineral and energy resource. India’s total trade with the region is only about 230 million (see the table). The recent failure of bid for PetroKazakhstan by OVL-Mittal combine only reinforced the impression that India lacks a clearly defined Central Asia policy. Influential circles feel that India’s policy is directionless, uncoordinated, unfocused and devoid of an over-all strategic intent.3